Antioxidant activity, total phenolic and flavonoid content of hevea brasiliensis clone / Nur Nadia Ramli - Ramli, Nur Nadia (Faculty of Plantation and Agrotechnology, 2018)
Rubber tree (Hevea brasiliensis) is an industrial crop from Euphorbiaceae family that grows in tropical climates and commonly known as an important economical commodity to Malaysia. However, there is little information available on its phytochemicals as well as their antioxidant activity. The aims of this study is to determine the extraction yield of different clone of rubber tree as well as to determine the antioxidant activity, total phenolic and flavonoid content from leaves and seeds extracts. The leaves and seeds extraction process was optimized by varying different parameter’s such as drying temperature, types of solvent used and temperature of extraction. The drying process was done at temperature of 70℃ for 24 hours. The dried samples were macerated with methanol and extraction was performed in a water bath at 60℃ using rotary evaporator. The percentage of crude methanol extract yield was based on the weight of dried plant materials. The determination of antioxidant was assessed by using the DPPH assay method. The total phenolic and flavonoid content was determined by using Folin-Ciocalteau assay and aluminium chloride colorimetric assay respectively. From this study, the result indicates that, the highest extraction yield was seeds extract (29.77%) from clone RRIM 2020. The highest amount of antioxidant was (79.16) from clone RRIM 2025. Therefore, the highest amount for total phenolic and flavonoid content was clone RRIM 2020 (0.020) and RRIM 3001 (0.200) respectively. As a conclusion, it showed that each clone gives a different result on each of the analysis.